SLEEP QUALITY IN PSYCHIATRIC INPATIENTS: MODERATING EFFECT OF ENVIRONMENT - Pyrke, Ryan (My University, 2015)
Inpatients with severe forms of mental illness including: depression and bipolar disorder, anxiety disorders, as well as schizophrenia and related disorders, experience severely disturbed sleep during their stay in hospital. Few interventions exist to treat poor sleep quality and those that do are not very effective in addressing this issue. We examined both objective and subjective sleep quality before and after a move from a ward-style mental health facility to a state-of-the-art integrated psychiatric hospital. Here, we address a major confound in the sleep literature concerning sleep quality in psychiatric inpatients by demonstrating that changes in the environment improve objective sleep quality. In line with previous research, measures of subjective sleep quality do not show this effect. Our results indicate that the redevelopment of psychiatric facilities is warranted and that evidence-based design features such as single-patient bedrooms should be chosen to maximize sleep quality of psychiatric inpatients.